2017
DOI: 10.1038/s41598-017-09901-y
|View full text |Cite
|
Sign up to set email alerts
|

Drastic Improvement in Adhesion Property of Polytetrafluoroethylene (PTFE) via Heat-Assisted Plasma Treatment Using a Heater

Abstract: The heating effect on the adhesion property of plasma-treated polytetrafluoroethylene (PTFE) was examined. For this purpose, a PTFE sheet was plasma-treated at atmospheric pressure while heating using a halogen heater. When plasma-treated at 8.3 W/cm2 without using the heater (Low-P), the surface temperature of Low-P was about 95 °C. In contrast, when plasma-treated at 8.3 W/cm2 while using the heater (Low-P+Heater), the surface temperature of Low-P+Heater was controlled to about 260 °C. Thermal compression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…It was previously reported that plasma treatment at low temperature (below 100 C) has a little effect on the adhesion property of PTFE and HAP treatment (above 200 C) has a signicant effect on its adhesion property. [20][21][22] Thus, the surface of each PTFE sheet was modied via HAP treatment according to the protocol reported previously. 21 However, in this study, the air concentration was controlled by the base pressure (as shown in ESI-1 †) during the HAP treatment.…”
Section: Heat-assisted Plasma (Hap) Treatment Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was previously reported that plasma treatment at low temperature (below 100 C) has a little effect on the adhesion property of PTFE and HAP treatment (above 200 C) has a signicant effect on its adhesion property. [20][21][22] Thus, the surface of each PTFE sheet was modied via HAP treatment according to the protocol reported previously. 21 However, in this study, the air concentration was controlled by the base pressure (as shown in ESI-1 †) during the HAP treatment.…”
Section: Heat-assisted Plasma (Hap) Treatment Methodsmentioning
confidence: 99%
“…HAP treatment involves applying heat to the PTFE surface by plasma treatment to induce surface hardening and introduce oxygen-containing functional groups. 20,21 HAP treatment has been shown to effectively improve both the indirect adhesion using an adhesive and direct adhesion (without an adhesive) of PTFE to other materials. 22 However, the HAP treatment in the previous studies was a leaf-type process: the pressure in the chamber was reduced to below 10 Pa using a rotary vacuum pump, and helium (He) gas was subsequently owed into the chamber until it reached atmospheric pressure (101 300 Pa).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a concern in this method due to serious environmental pollution and thus hurts the human body health . What is more, it may blacken the surface and reduce surface resistance of PTFE in high temperature environment . Therefore, the alternative approach of hole metallization pretreatment over PTFE with improved quality for high‐frequency and environmental‐friendly waste is absolutely desirable.…”
Section: Introductionmentioning
confidence: 99%